Given the system of equations:
![\begin{gathered} y=(1)/(3)x+4 \\ \\ y=-3x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ntluyd3l0me5dbyp1orrowo57b8msv4hk0.png)
Ley's determine if the system is inconsistent or consistent and dependent or independent.
Let's first solve the system of equations.
Eliminate the equivalent sides and combine the equations.
We have:
![\begin{gathered} (1)/(3)x+4=-3x+2 \\ \\ (x)/(3)+3x=2-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4fkwfbutpwyvvz0yu2u4712uyxi3im9r4l.png)
Solving further:
![\begin{gathered} (x+9x)/(3)=-2 \\ \\ (10x)/(3)=-2 \\ \\ Multiply\text{ both sides by 3:} \\ (10x)/(3)*3=-2*3 \\ \\ 10x=-6 \\ \\ Divide\text{ both sides by 10:} \\ (10x)/(10)=-(6)/(10) \\ \\ x=-(3)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hf4naaxc8g6r3jwgvdnxfdf2aoibf150yz.png)
Now, plug in -3/5 for x in any of the equations:
![\begin{gathered} y=(1)/(3)x+4 \\ \\ y=(1)/(3)*(-(3)/(5))+4 \\ \\ y=-(1)/(5)+4 \\ \\ y=(-1+20)/(5) \\ \\ y=(19)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gf1x5yx25jc5fe160fpjdmrsyls45survi.png)
Therefore, we have the solutions:
![(x,y)==>(-(3)/(5),(19)/(5))](https://img.qammunity.org/2023/formulas/mathematics/college/so925bmeyr8k0x69lzb6q875uk9rm7tvvd.png)
The system is consistent and independent since it has a definite solution.
The system has just one solution, so we can say it is consistent and independent.
ANSWER:
Consistent and independent.